Riedel's Thyroiditis in Multifocal Fibrosclerosis: CT and MR Imaging Findings - Özgen, Ali; Cila, Aysenur (American Journal of Neuroradiology, 2000)
Summary: Riedel's thyroiditis is a rare disorder of unknown etiology and may be seen isolated or as a part of multifocal fibrosclerosis. It is important to distinguish Riedel's thyroiditis from thyroid carcinoma. Reports about imaging features of Riedel's thyroiditis are limited in the radiologic literature. We describe herein CT and MR imaging features of Riedel's thyroiditis in a case of multifocal fibrosclerosis with previously unreported radiologic observations.